The Impact of ESG Ratings on Investment Decisions in the Energy Sector During Uncertain Times - Tlaty, Mamdouh; Mahdi, El Idrissi El; Marouane, Nakhcha; Ouahi, Younes (European Scientific Journal, ESJ, 2024)
With increasing global awareness of sustainability, the financial sector must inevitably adapt. Our research investigates the role of Environmental, Social, and Governance (ESG) ratings in investment decision-making, particularly in the energy sector, by examining their impact on portfolio performance. The study aims to assess the impact of ESG integration on portfolio risk and returns. Using data from the SP500 index, econometric models and Monte Carlo simulations are employed to evaluate how ESG considerations influence portfolio optimization and risk management. The study reveals that integrating ESG criteria into investment strategies, especially during market volatility, may not always directly affect returns, they provide significant benefits in terms of risk mitigation and ethical investment alignment.